Librarians Competence Improvement through Outbound Staff Mobility (OSM) in Institut Teknologi Sepuluh November - Mindart, Lely Indah; Triwidiyawati, Anita; Anggiasari, Tiara (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
In the disruption era, libraries are required to be able to innovate and adapt to rapid changes. This condition was responded to by Institut Teknologi Sepuluh November’s (ITS) Library by implementing Outbound Staff Mobility (OSM) program. OSM was first initiated in 2013 and continues till today. The study describes the implementation of OSM at ITS Library in order to improve librarian competence. The data was obtained through interviews with OSM organizers, the head of ITS library, and ITS librarians who have engaged during 2013-2018. In addition, the data were also obtained through observation and documentation. The data analysis used the Creswell data analysis model. OSM program has implemented well. It can be seen from the effectiveness of the clarity of the objectives to be achieved, the clarity of the strategy for achieving objectives, the process of analysis and policy formulation, careful planning, proper programming, the availability of facilities and infrastructure, and the availability of a monitoring system and control. In addition, it has impacted on increasing the professional competence of librarians, such as increasing insight in managing services, utilizing information technology, providing guidance and assistance, and management of problems through creative ideas and innovation.